ACADEMIC SUPERVISION IN IMPROVING TEACHERS’ SKILLS DURING THE LEARNING PROCESS AT ELEMENTARY SCHOOL - Endriani Endriani; Fefi Yulita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The principal has an obligation to be able to improve the quality of teacher in the learning process at school. Based on the observations, it was found that the number of learning processes carried out by elementary school teachers at schools were not in accordance with the characteristics of elementary school students, so that improvements were needed to improve the skills of these teachers. The purpose of this study was to determine the improvement of teachers’ skills in the learning process at elementary schools through academic supervision activities. This research was a classroom action research that adapted the design of Mc Taggart and Kemmist's classroom action research. This research consisted of stages of planning, implementation, observation and reflection. The findings stated that there was an increase in the implementation skills of the teacher's learning process by getting an average score of 68.46 in cycle 1 and increased to 86.10 in cycle 2. This proved that there was an increase in teachers’ skills in the learning process at elementary schools through academic supervision activities. The implications of this research was that it could be used as a basis by supervisors to be able to improve teachers’ skills in the learning process at elementary schools.